1) 2cos5x-sqrt{3}=0
2)2sin+frac{x}{4}1=0
3)sqrt{2}(frac{pi}{6}-4x)+1=0
4)-2tg(-frac{3x}{2}=2
5)cosx cos2x-sinx sin2x=-1
6)frac{2sinx+sqrt{3}}{cos8x-8}=0
2x+3y=16 x=(16-3y)/2 x= (16-3y)/2 x=(16-3y)/2
{ { { {
3x-2y=11 3x-2y=11 (48-9y)/(2) - 2y=11 (48-9y-4y)/(2)=11
x=(16-3y)/2 x=(16-3y)/2 x=(16-3y)/2 x=(16-6)/2 x=10/2 x=5
{ { { { { {
(48-13y)/2=11 48-13y=22 26=13y y=2 y=2 y=2.
1) 2cos5x-sqrt{3}=0
2)2sin+frac{x}{4}1=0
3)sqrt{2}(frac{pi}{6}-4x)+1=0
4)-2tg(-frac{3x}{2}=2
5)cosx cos2x-sinx sin2x=-1
6)frac{2sinx+sqrt{3}}{cos8x-8}=0
1) cos5x = /25x = +- П/6 +2Пkx = +-П/30 +2Пk/5 2,3 - не поняла запись (там не всего хватает) 4) 5) cosx 6)